Melts and fluids evolution in the process of crust and mantle formation in Paleo-Proterozoic (2,2—1,75 Ga ago). Stratigraphy and magnetic activity - O. V. Usenko (Геофизический журнал, 2017)
Stratigraphy of metamorphic Precambrian complexes related to Paleo-Proterozoic is controversial. An additional sign permitting to correlate strata may be their material composition because in the Precambrian composition of deep fluids changed regularly. Then some regularity in changes of composition of magmatic and metamorphic rocks has to exist. The rocks produced during this time are dolomite and calcite. Quartzite, carbonaceous shist and graphite gneiss are also abundant. Only during this activation of Precambrian carbonatite volcanic activity became apparent.